Theory and Method in Higher Education Research - Pinho, Isabel (Educar em Revista, 2019)
Because I have learned a lot from reading the two previous books in this collection, organized by the Professors Malcon Tight and Huisman (Tight & Huisman, 2015, 2016), I also decided to read Volume 3 of Theory and Method in Higher Education Research (2017) and write this review, which I hope will be useful both for the novice and experienced researchers Higher Education Researchers and for those who are interested in studies that integrate theory and methodology, in several geographical spaces and interdisciplinary spaces.